ALGORITHM OF DIAGNOSTICS AND SURGERY OF TRAUMA AND DEGENERATIVE DISEASES OF CERVICAL SPINE - V. V. Shchedrenok; T. V. Zakhmatova; I. V. Zuev; O. V. Moguchaya; O. N. Tyulkin; N. V. Topolskova; K. I. Sebelev (Вестник хирургии имени И.И. Грекова)
A retrospective analysis of diagnostics and surgery in 240 patients was made. The vertebral spinal trauma took place in 168 patients (average age 31±5 years), degenerative dystrophic diseases of spine were in 72 patients (average age 52±7 years). The clinicodiagnostic complex included survey and functional radiography of the spine, magnetic resonance image and helical computer tomography of the spine with spondylometric measurements and color duplex scanning of the vertebral artery. Stabilization of the spine was performed in 137 (57%) cases. The variants were determined on the basis of predominate injury of 1 out of 3 supporting complexes. The rigid and dynamic methods and their combination were used for fixation of the spine. More favorable results were registered using dynamic fixation and the arthroplasty of intervertebral disks with nitinol constructions. An algorithm of radiodiagnostics and surgery methods were proposed.